Plasma Cytokines, Metabolic Syndrome, and Atherosclerosis in Humans. Issue 1 (1st January 2007) - Reilly, Muredach P.; Rohatgi, Anand; McMahon, Kimberly; Wolfe, Megan L.; Pinto, Shailesh C.; Rhodes, Thomas; Girman, Cynthia; Rader, Daniel J.
Abstract : Background: Interleukin-6 (IL-6) and tumor necrosis factor α (TNF-α) integrate inflammatory and adipose signaling but also have direct vascular effects. We hypothesized that plasma levels of IL-6 and soluble tumor necrosis factor α receptor 2 (sol-TNFR2) would be related to coronary atherosclerosis beyond established risk factors and the metabolic syndrome. Methods: We examined the association of IL-6 and sol-TNFR2 with metabolic syndrome, C-reactive protein (CRP), and coronary artery calcification (CAC) in 875 asymptomatic participants in the Study of Inherited Risk of Coronary Atherosclerosis. Results: IL-6 levels were 56% higher ( p < .001) and sol-TNFR2 levels 16% higher ( p < .001) in subjects with metabolic syndrome compared with those without. Both cytokines were associated with CAC beyond age, gender, Framingham risk scores, family history, metabolic syndrome, and CRP (odds ratio and 95% confidence interval of higher CAC for 1 SD increase in log-transformed cytokine levels: 1.23 [1.06-1.43], p = .006 for IL-6 and 1.15 [1.01-1.31], p = .04 for sol-TNFR2). In fact, cytokine levels were independently associated with CAC scores in the subgroup with metabolic syndrome and were additive to the homeostasis model assessment of insulin resistance in predicting CAC. Conclusions: Plasma IL-6 and sol-TNFR2 levels were independently associated with CAC, suggesting a role in integrating innate immune and adipose signaling in promoting atherosclerosis and cardiovascular risk. Measurement of their levels may facilitate cardiovascular risk prediction and targeting of therapeutic strategies.